Long-term Outcomes Following Lumbar Microendoscopic Diskectomy and Microendoscopic Decompression: Minimum 10-year Follow-up Evaluation Performed Using a Patient-based Outcome Measure - Aihara, Takato; Endo, Kenji; Suzuki, Hidekazu; Sawaji, Yasunobu; Urushibara, Makoto; Matsuoka, Yuji; Takamatsu, Taichiro; Murata, Kazuma; Kusakabe, Takuya; Maekawa, Asato; Ouchi, Juntaro (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Study Design Retrospective study of prospectively collected outcome data.Background No studies have evaluated the long-term outcomes following microendoscopic diskectomy for lumbar disk herniation (MEDH) and microendoscopic decompression for lumbar spinal stenosis (MEDS) using the Japanese Orthopaedic Association Back Pain Evaluation Questionnaire (JOABPEQ).Objective To assess the minimum 10-year outcomes following MEDH and MEDS.Patients and Methods Seventy-six patients were classified into three groups: disk herniation (DH) group (33 patients underwent MEDH); spinal stenosis (SS) group (23 patients underwent MEDS); and degenerative spondylolisthesis (DS) group (20 DS patients underwent MEDS). The follow-up rate was 50.3% (76/151). The results were statistically compared using Scheffé's F test for differences among the DH, SS, and DS groups. The paired t test was used to compare the preoperative and postoperative visual analog scale (VAS) scores. The degrees of improvement (DOIs) on JOABPEQ and the intensities of improvement (IOIs) on VAS at the first follow-up evaluation (FFE) (mean: 12 months after the operation) and at the most recent follow-up evaluation (MRFE) (mean: 126 months) of the DH group were statistically compared by the paired t test. DOIs and IOIs at MRFE of the SS group (mean: 126 months) and DS group (mean: 125 months) were statistically compared by the unpaired t test. A p value < 0.05 was considered statistically significant.Results Statistical comparisons of the DOIs in all five functional scores and IOIs in low back pain (LBP), leg pain, and leg numbness showed no significant differences among the DH, SS, and DS groups. The effectiveness rates of pain-related disorders, gait disturbance, and social life disturbance in JOABPEQ were almost equally high in all three groups. Significant decreases in LBP, leg pain, and numbness, as measured with VAS, were noted at MRFE in all three groups. No significant differences were observed between FFE and MRFE concerning the DOIs and IOIs of the DH group, and between the SS and DS groups concerning the DOIs and IOIs at MRFE.Conclusion Clinical 1-year outcomes of MEDH were thought to be maintained for  > 10 years, and MEDS leads to the same clinical long-term outcomes with DS as without DS. Moreover, MEDH and MEDS were almost equally effective for  > 10 years not only in improving LBP, leg pain, and numbness but also especially in improving pain-related disorders, gait disturbance, and social life disturbance by detailed quality-of-life assessment using JOABPEQ.
Keywords: patient-based outcome measure; microendoscopic diskectomy; microendoscopic decompression; minimum 10-year follow-up; reoperation rate